รูปแบบการให้แสงสว่างประดับตกแต่งสำหรับมัสยิดเขตธนบุรีในกรุงเทพมหานคร - รัชดา สุวรรณางกูร (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Mosque or Masjid is a Muslim place of worship. Its architecture is unique and expresses the culture of Muslim peoples in the past. Significant Mosques in several countries were decoratively illuminated at night. However, decorative lighting for Mosques in Thailand is rarely seen and lighting design patterns on these Mosques are unlikely to be identified. This research was to study and categorized the architectural elements of the Mosques leading to decorative lighting design recommendation for the Mosques in Thonburi. Some of the Mosques in this area are historic buildings. They are also architectural heritage and serve as landmarks of their communities. 24 Mosques were selected to study their history and architectural elements. These data were sorted, analyzed and categorized. Then, 5 Mosques representing each category were selected to find the alternative lighting design patterns. The major architectural elements of the Mosques; dome, arch (main entrance and Islamic arcade) and minaret, were analyzed using architectural design fundamental. Sites and surroundings of the Mosques were also in consideration. Next, alternative lighting design patterns of each element were applied to these Mosques via computer simulation program. Moreover, Likert scale method was used in the form of questionnaires to determine both Buddhist and Muslim people’ perception. Five adjectives of senses were asked: light, beautiful, visually comfortable and enhancing the Mosque to find appropriate decorative lighting patterns for each case. It was found that to illuminate the Mosque, site and its surroundings must be considered. Then, the decorative lighting patterns should enhance on its major architectural elements by means of various lighting design techniques such as floodlighting, silhouetting and spotlighting, etc. The minor elements may also be lit to enhance more details. The lighting design recommendation in this study can be applied to other Mosques or similar types of architecture.